RESTRICTION SITE MAPPING OF ERWINIA CAROTOVORAEXTRACHROMOSOMAL ELEMENT PCA25 - Ж. Ю. Сергєєва; Ф. I. Товкач (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2009)
The restriction site mapping of Erwinia carotovora extrachromosomal element pCA25 and its transposon variant рCA25::Tn9 has been carried out. The preliminary restriction map of the plasmid has been created and the site of the Tn9 transposon incorporation has been detected corresponding to the obtained data.